GAME LEGENDA ASAL MULA DANAU TOBA BERBASIS DESKTOP - Febri Maspiyanti; Indah Erika Sulistya (Jurnal TAM (Technology Acceptance Model), 2018)
Game can be used as media to implement play activity. The Legend of Toba Lake game is a game that created to preserve the existing legend back on the island of Sumatra, especially North Sumatra Province. This game created using Unity 3D with desktop-based adventure game theme. This game brings the history plot of Toba Lake as a background story. In this game, there are five 3D scenes based on the Toba Lake plot twist story. In this study, we use Fisher Yates Shuffle algorithm for the questions randomization. In order to accompolish the game plot, the player have to complete all the mission in each scene.